Worsened Financial Situation During the COVID-19 Pandemic Was Associated With Depressive Symptomatology Among University Students in Germany: Results of the COVID-19 International Student Well-Being Study - Negash, Sarah; Kartschmit, Nadja; Mikolajczyk, Rafael T.; Watzke, Stefan; Matos Fialho, Paula Mayara; Pischke, Claudia R.; Busse, Heide; Helmer, Stefanie M.; Stock, Christiane; Zeeb, Hajo; Wendt, Claus; Niephaus, Yasemin; et al. (Frontiers in Psychiatry, 2021)
Background: Previous findings suggest that university students are at an elevated risk to experience financial hardship and to suffer from depressive symptoms. This vulnerability may have substantially increased during the COVID-19 pandemic which might have affected students’ socio-economic situation but possibly also their mental well-being. We examined whether the financial situation changed during the COVID-19 pandemic among German university students, and whether changes were associated with mental well-being. Methods: We conducted a cross-sectional online survey in May and July 2020 at five German universities. Participants were asked, if they had sufficient financial resources to cover monthly expenses before and during the pandemic. The answer options were dichotomized into worsened and no change/ better financial situation compared to before the COVID-19 pandemic. Depressive symptoms were assessed using the CES-D 8 scale. For examining associations between sociodemographic, study-related and financial factors and “worsened financial situation”, we ran a generalized linear mixed model. To assess associations between depressive symptoms and worsened financial situation, we performed a linear mixed model. Results: We included 7,199 participants in the analyses (69% female, 30% male, 1% diverse, mean age: 24 years, standard deviation: 4.7). Overall, 25% of the participants reported to have a worsened financial situation at the time of the survey than in the time before COVID-19. Factors associated with a worsened financial situation were migration background, parents not being academics, not being able to borrow money, and payment of tuition fee by student and loan (Odds Ratios (OR) ranging from 1.20 to 2.35). Factors associated with lower odds were: being single, living with others, studying a health-related field, being enrolled in a doctoral/ PhD or state exam program, and publicly funded tuition/ tuition paid with a scholarship (OR ranging from 0.42 to 0.80). A worsened financial situation was associated with 1.02 points more on the CES-D 8 scale (95% CI: 0.80- 1.24). Conclusion: Our results suggest that the pandemic put a number of students under financial strain with detrimental consequences for their mental well-being. Renewed attention must be paid to this vulnerable group to prevent the potentially damaging effects on their mental health.